Wheat Variety Response to Seeding Rate in Kansas During the 2018–19 Growing Season - R. P. Lollato; L. Molssato; C. Rapolla; G. Zhang; A. Fritz (Kansas Agricultural Experiment Station Research Reports, 2019)
Different wheat varieties might require different seeding densities to maximize yield. Thus, the main objective of this project was to better understand the response of different wheat varieties to different seeding rates. Three field experiments were conducted during the 2017-18 growing season evaluating six wheat varieties subjected to five different seeding rates (0.6, 0.95, 1.3, 1.65, and 2.0 million seeds per acre). Crop was managed from a 70 bu/a yield goal and pests were controlled using commercially available pesticides. We measured final stand and grain yield, and all statistical analyses were performed for relating emerged plants per acre to grain yield. At each individual environment and across varieties, grain yield usually maximized at approximately 0.9 million emerged plants per acre. There were significant differences among varieties in grain yield, with Joe and Tatanka usually outperforming the remaining tested varieties. Across environments, grain yield usually maximized at populations between 0.6 and 0.7 million plants per acre for less responsive varieties (1863, Everest, and Tatanka), at approximately 0.9 million plants per acre for average responsive varieties (Joe, Bob Dole, KanMark, and Zenda), and greater than 1.05 million emerged plants per acre for more responsive varieties (Larry and AG Icon). These preliminary data suggest that there is the potential to manage each wheat variety according to its individual tillering potential, but more data are needed to take definite conclusion about each variety’s optimum seeding rate. Thus, this experiment is being conducted at five sites during the 2017-18 growing season.
Keywords: wheat; variety; seeding rate; plant population; yield